Here's my problem and I think I'm close but welcome any comments/corrections.

Solve for the unknown variable.

6e^-3t = 3

--------------------------------------

6e^-3t = 3

e^-3t = 3/6

ln e^-3t = ln 3/6

-3t = ln 3/6

t = ln 3/6 /-3

Here's my problem and I think I'm close but welcome any comments/corrections.

Solve for the unknown variable.

6e^-3t = 3

--------------------------------------

6e^-3t = 3

e^-3t = 3/6

ln e^-3t = ln 3/6

-3t = ln 3/6

t = ln 3/6 /-3

Solve for the unknown variable.

6e^-3t = 3

--------------------------------------

6e^-3t = 3

e^-3t = 3/6

ln e^-3t = ln 3/6

-3t = ln 3/6

t = ln 3/6 /-3

- Martingale
**Posts:**335**Joined:**Mon Mar 30, 2009 1:30 pm**Location:**USA-
**Contact:**

hbelle wrote:Here's my problem and I think I'm close but welcome any comments/corrections.

Solve for the unknown variable.

6e^-3t = 3

--------------------------------------

6e^-3t = 3

e^-3t = 3/6

ln e^-3t = ln 3/6

-3t = ln 3/6

t = ln 3/6 /-3

if your answer is

then you are good

Please help me understand

why the ln(3/6) changed to ln2 and

what happened to the negative -3, why did it change to positive?

thanks!

why the ln(3/6) changed to ln2 and

what happened to the negative -3, why did it change to positive?

thanks!

Oh, log rule ln(x/y) = ln(x) - ln(y)

So:

-ln(3/6) becomes -ln(1/2)

= -(ln(1) - ln(2)) = - (0 - ln(2)) = ln(2)

So:

-ln(3/6) becomes -ln(1/2)

= -(ln(1) - ln(2)) = - (0 - ln(2)) = ln(2)